2014
DOI: 10.1016/j.neuroimage.2013.12.025
|View full text |Cite
|
Sign up to set email alerts
|

Upper limb motor rehabilitation impacts white matter microstructure in multiple sclerosis

Abstract: Upper limb impairments can occur in patients with multiple sclerosis, affecting daily living activities; however there is at present no definite agreement on the best rehabilitation treatment strategy to pursue. Moreover, motor training has been shown to induce changes in white matter architecture in healthy subjects. This study aimed at evaluating the motor behavioral and white matter microstructural changes following a 2-month upper limb motor rehabilitation treatment based on task-oriented exercises in pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
89
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(92 citation statements)
references
References 66 publications
1
89
2
Order By: Relevance
“…To this aim, we believe that active rehabilitation, based on voluntary task-oriented exercises, could determine beneficial effects in terms of functional independence. In agreement with this assertion, Bonzano et al demonstrated that rehabilitation treatment based on voluntary movements may contribute to preserve the white matter integrity in the corpus callosum and corticospinal tracts and to maintain the coordination ability; such benefits were not observed in control group [27]. These findings confirms the hypothesis that the sensorimotor deficits observed in PwMS over the disease course could be mainly due to the progression of white matter damage and that neurorehabilitation may attenuate this neurodegenerative process [37,38].…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…To this aim, we believe that active rehabilitation, based on voluntary task-oriented exercises, could determine beneficial effects in terms of functional independence. In agreement with this assertion, Bonzano et al demonstrated that rehabilitation treatment based on voluntary movements may contribute to preserve the white matter integrity in the corpus callosum and corticospinal tracts and to maintain the coordination ability; such benefits were not observed in control group [27]. These findings confirms the hypothesis that the sensorimotor deficits observed in PwMS over the disease course could be mainly due to the progression of white matter damage and that neurorehabilitation may attenuate this neurodegenerative process [37,38].…”
Section: Discussionmentioning
confidence: 63%
“…The rehabilitative treatment was tailored to the specific individual needs and was planned on volitional tasks mainly focused on motor performances. We kept into account the assertion that potential changes are specific to a given task and not a general effect of any training [27,28]. PwMS were treated according to a protocol based on voluntary exercises for neuromuscular control, aimed to improve muscle strength of both upper and lower limbs, propioceptive sensibility, stability and coordination for balance.…”
Section: Rehabilitation Programmentioning
confidence: 99%
“…In active group the bimanual coordination task remained stable, while worsened in passive group. Accordingly in fMRI, passive group, but not active one, showed reduced fractional anisotropy and increased radial diffusivity of corticospinal tracts and corpus callosum [63].…”
Section: Pappalardo Et Al Mult Scler and Demyelinating Dismentioning
confidence: 77%
“…Four of seven studies (57%) had active comparison groups, [19][20][21][22] and the remaining three had usual care 23,24 or no intervention control groups. 25 The number of intervention sessions ranged from 10 25 to 24 24 over 2 25 to 8 24 weeks.…”
Section: Task-oriented Training/neurorehabilitation Principlesmentioning
confidence: 99%
“…20,21,24,25 The most commonly excluded comorbidities were cognitive impairment (n = 4, 57%) 20,21,24,25 and psychiatric disorders (n = 3, 43%) 20,21,24 (Figure 3). These psychiatric disorders were not identified.…”
Section: Task-oriented Training/neurorehabilitation Principlesmentioning
confidence: 99%